Integration of whole life cycle costing with sustainable facilities management for privatized building projects in Malaysia - Khiyon, Noor Azeyah (2019)
Privatized building projects are escalating in Malaysia and render the importance of Whole Life Cycle Costing (WLCC) and Sustainable Facilities Management (SFM) as these are the two main features of the projects. However, in Malaysia, the guideline for these projects focuses only on WLCC but not on SFM, thus jeopardizing the maintenance culture. Additionally, Malaysia lacks standardized procedures for implementing WLCC and SFM. Therefore, this research examined the barriers and drivers of WLCC and SFM for privatized building projects in Malaysia, investigated the parameters of WLCC and SFM relevant to these projects, proposed a framework of WLCC of SFM for these projects and validated the proposed framework. In order to achieve the intended objectives of the research, the quantitative method was adopted, whereby self-administered questionnaires were utilized. Since the population of the respondents of the research is relatively small, hence, no sampling was required. The questionnaires were distributed to all the members of Malaysian Association of Facility Management (MAFM). The results revealed that the main barrier that hindered the WLCC implementation in the projects was the inconsistency in underlying philosophy and methodology whereas for SFM, there was a lack of guidance in the documentation. In order to drive the implementation of both WLCC and SFM, the findings showed that it is essential to define WLCC parameters and assumptions, besides reducing the life cycle costing for SFM. Additionally, the findings disclosed significant parameters of WLCC and SFM, which led to the development of a framework of WLCC of SFM for the projects. The framework was validated by means of a Delphi survey that revealed the satisfaction of all the panel of experts. In conclusion, the research contributes by means of developing a framework of WLCC and SFM, adjudged to have the potential to systematically guide the facility managers in implementing WLCC of SFM for privatized building projects in Malaysia to enable them to succeed in terms of monetary as well as sustainability.